Diagnostic strategy of fine needle aspiration cytology of cystic cervical lymph node metastasis from papillary thyroid carcinoma. Issue 7 (12th April 2022) - Li, Qin; Liu, Ying; Zhang, Guofu; Long, Hu; Jiang, Yong; Su, Xueying
Abstract: Background: Cystic cervical lymph node metastasis from papillary thyroid carcinoma (CLMPTC) initially presents as cervical cystic lesions, which are often underdiagnosed as other cystic cervical lesions. There is no comprehensive diagnostic strategy of fine needle aspiration (FNA) cytology for CLMPTC. Methods: The clinical and FNA cytomorphology data of 87 patients with CLMPTC were analyzed. Thyroglobulin (TG) immunostaining was performed in 40 cases; BRAF V600E mutation was evaluated in 42 cases; the thyroglobulin (Tg) levels of aspiration fluids were assessed in 46 cases. Correspondingly, the data of 42 cases with solid cervical lymph node metastasis from papillary thyroid carcinoma (SLMPTC) and 32 cases with other cystic cervical lesions were collected as controls. Results: Compared with SLMPTC, CLMPTC has less classical PTC cytomorphology characteristics—for example, nuclear crowding/overlapping, nuclear irregular contours, etc. ( p < .05). Additionally, micropapillary architecture and histiocyte‐like tumor cells were more often observed in CLMPTC than in SLMPTC ( p < .01). The positive rate of TG immunocytochemistry in CLMPTC was 100% (40/40). The positive rate of BRAF V600E mutation in CLMPTC was 81.0% (34/42), which was higher than that in SLMPTC (64.3%; 27/42) ( p = .087). The Tg levels in aspiration fluids were significantly higher in CLMPTC (all>500 μg/L) than in other cervical cystic lesions (range: 2.9 μg/L to 40.1 μg/L) ( p < .01). Conclusion: To reduce underdiagnoses of CLMPTC, a reasonable diagnostic strategy, as summarized in this study is needed: according to the number of tumor cells, choosing immunocytochemistry (TG) and/or thyroglobulin in fine needle aspirates testing as auxiliary diagnostic measures.